Social Science Research and Everyday Human Life - Upadhyay, Prakash (Journal of Nepalese Business Studies, 2018)
Pedestaled on qualitative secondary data congregated from secondary sources, the major objective of this paper is to analyze relation between social science research and daily human life especially with problem solving and decision making activities. The key argument of this paper is that social science research attempts to find social patterns of regularity in social life that usually deals with social group. Yet, in social science there are no social laws parallel to natural science laws. A law in social science is a universal generalization about a class of facts. There are diverse schools of thought embedded with key perspectives in social research. Social researchers inquire and wonder on diverse issues and matters in everyday human life. By means of sense and inquisi tive knowledge background they explore the raison d'être behind any issue. And it is the systematic research probing the reasons behind the issues tremendously germane in daily life. In our daily life we put up with copious tribulations, research knowledge and the solutions of the problems emerging from researches prove handy and practical for the society and the people. This study deduced that, improving the quality of every day social life is a significant goal since the pools of ideas configures much philosophy and much telling about society, by social scientists and by others. Hence, in having a comprehension of debates and the applicability of different methods of research and the implications of research findings on society, advanced researches and more inquiring and confident researchers will be more productive. The Journal of Nepalese Business Studies Vol. X No. 1 December 2017, Page: 28-41